Lack of t(14; 18) polymerase chain reaction-positive cells in highly purified CD34+ cells and their CD19 subsets in patients with follicular lymphoma - Voso, Maria Teresa; Hohaus, Stefan; Moos, Marion; Haas, Rainer (Blood, 1997)
Follicular lymphoma (FL) is characterized in a significant proportion of cases by the t(14; 18) chromosomal translocation, which results in the juxtaposition of the oncogene bcl-2 to the joining region of the immunoglobulin heavy chain (IgH) gene. Molecular sequence analysis indicates that the t(14; 18) rearrangement occurs in a B-lymphoid progenitor cell at the time of IgH rearrangement. We were interested whether hematopoietic stem and progenitor cells as characterized by CD34 expression bear the translocation. Bone marrow (BM)-CD34+ cells were enriched from 14 patients with FL whose BM was known to be positive for bcl-2/IgH (major breakpoint region [MBR]). Six patients were in complete remission (CR), two patients were in partial remission (PR), and six patients had active disease. Six patients had histological BM involvement when the samples were obtained. Using an immunomagnetic selection device (MINIMACS), a mean purity of 88.7% ± 4% CD34+ cells was achieved. The CD34+ cells were further enriched by fluorescence activated cell sorting (FACS) using CD34 fluorescein isothiocyanate (FITC)- and CD19 phycoerythrin (PE)-conjugated antibodies. The IgH gene was rearranged in the CD34+/CD19+ cell subset of all patients assessed by polymerase chain reaction (PCR). This population is thought to represent the progenitor stage at which the bcl-2/IgH translocation occurs. The unseparated BM mononuclear cell fraction from all 14 patients was positive for bcl-2/IgH using a nested PCR, but the BM-CD34+ cell fraction and the respective CD34+/CD19+ subset were negative in 13 of these 14 patients. The one patient with a positive PCR signal in the CD34+ cell subset had a relapse with BM involvement. We conclude that CD34+ progenitor cells including CD34+/CD19+ B-cell progenitors are not involved in the malignant cell clone. These data are in agreement with a transgenic mouse model, which indicates that the malignant phenotype in FL is sustained by mature B cells.
Elektronische Reproduktion der Druck-Ausgabe 14. Dezember 2020
Gesehen am 13.05.2025